QADIMGI XORAZM TARIXIGA OID ARXEOLOGIK TADQIQOTLAR - Ochilova Jasmina, Ergasheva Nargiza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In the article,information the separation of the ancient khorezm state from the Achaemenids and the development of handicrafts and other industries.